Control speed of BLDC motor using PID - Mahmud, Md; Islam, Md Rafiqul; Motakabber, S.M.A.; Abdus Satter, Md Dara; Afroz, Khan Elnas; Habib, A. K. M. Ahasan (IEEE, 2022)
The current development of science, technology, and industrial revolutions did not happen suddenly. Many years of empirical investigation efforts by human intelligence have brought the world to its present state. As a result, new technologies and innovations would move human civilization to a more advantageous position every day. One of the other remarkable inventions of the present day is the brushless DC (BLDC) motor. The BLDC motors can play a huge role in making the industry most dynamic in the future. It has many advantages over conventional DC and AC motors. However, BLDC motors have been used in various electrical and electronic devices. The BLDC motors need a suitable control driver system to control the speed and torque to get better performance. This study utilizes the MATLAB-Simulink software to develop a combination of propositional integral derivative (PID) controllers that help control the BLDC motor’s speed more efficiently. Enhancement of the capacity of the PID controller is the main agenda of this paper. Finally, the study has undergone some tests to verify whether the BLDC motor using the PID system is more suitable and efficient than other controllers.